Validation of the Brief Symptom Inventory–18 Among Low-Income African American Adolescents Exposed to Community Violence - Kim, Dong Ha (Journal of interpersonal violence, 2021)
African American youth, especially those who reside in low resourced communities, are exposed to higher levels of exposure to community violence relative to their counterparts from other race/ethnic groups. However, appropriate measures for assessing psychological stress related to such exposures are underresearched in the extant literature for this population. The aim of the current study was to examine the reliability and validity of the Brief Symptom Inventory (BSI-18) scale among African American youth exposed to community violence through classical test theory and item response theory methods. Internal reliability and construct validity were examined. Results indicated good internal reliability (α = .93). Construct validity of the BSI-18 was established through confirmatory factor analysis with the three-factor somatic, depression, and anxiety model. Construct validity was also determined with all items indicating adequate fit. Our study indicates good reliability and validity of the BSI-18 to assess psychological distress among African American youth exposed to community violence.